1998
DOI: 10.1002/j.1551-8833.1998.tb08433.x
|View full text |Cite
|
Sign up to set email alerts
|

SDWA capacity development

Abstract: Using stakeholder comments, USEPA is creating guidance and information to smooth implementation of SDWA capacity development provisions. The capacity development provisions of the 1996 Safe Drinking Water Act offer a flexible framework within which states and water systems can work together to ensure that systems acquire and maintain the technical, financial, and managerial capacity needed to consistently achieve the public health protection objectives of the act. Capacity development is related to the Drinkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…Interestingly, capacity for water management is just as much a concern in ''developed'' countries such as the United States and Canada as it is in so-called ''developing'' countries. For example, 1996 amendments to the United States Safe Drinking Water Act (SDWA) drew attention in that country to a serious problem: the ability or capacity of water treatment plant operators in small communities to meet strict standards created under the 1986 SDWA (Shanaghan et al, 1998;United States Environmental Protection Agency [USEPA], 1998).…”
Section: Community Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, capacity for water management is just as much a concern in ''developed'' countries such as the United States and Canada as it is in so-called ''developing'' countries. For example, 1996 amendments to the United States Safe Drinking Water Act (SDWA) drew attention in that country to a serious problem: the ability or capacity of water treatment plant operators in small communities to meet strict standards created under the 1986 SDWA (Shanaghan et al, 1998;United States Environmental Protection Agency [USEPA], 1998).…”
Section: Community Capacitymentioning
confidence: 99%
“…Similarly, Litke and Day (1998) suggested that a lack of financial resources can reduce the capacity of agencies, organizations, and citizens to complete effective watershed planning. In this paper, financial capacity is defined in terms of the ability to generate and access funding (Goodman et al, 1998;de Loe¨et al, 2002); the presence of adequate resources to meet operating expenses and manage water supplies (Shanaghan et al, 1998;de Loeë t al., 2002); the sustainable and prudent use of financial resources including the use of market mechanisms to influence behavior and reduce demand for water supplies (Hamdy et al, 1998); and financial flexibility, which affects the ability of local governments to adapt to changing circumstances (Mead, 1986). Specific indicators of financial capacity are provided in Table 1.…”
Section: Technicalmentioning
confidence: 99%
“…For instance, de Loë et al (2002) evaluated the groundwater management capacity of several small Ontario municipalities, using institutional, financial, technical, social, and political criteria. A further example is the requirement under the US Safe Drinking Water Act (SDWA) for public water suppliers to demonstrate technical, financial, and managerial capacity in order to qualify for funding from the Drinking Water State Revolving Fund (Shanaghan et al, 1998). The US Environmental Protection Agency (EPA) defines capacity in terms of three aspects: (1) technical capacity (referring to the quality and appropriateness of infrastructure, along with the skills and abilities of water system personnel); (2) managerial capacity (relating to the system's institutional and administrative capabilities); and (3) financial capacity (the ability to acquire and manage financial resources) (US EPA, 1998).…”
Section: Capacity For Groundwater Managementmentioning
confidence: 99%
“…Local governments commonly derive financial resources from the tax base, as well as from grants and loans from senior government agencies. In the water sector, financial resources can be targeted to water system expenditures (infrastructure, maintenance, and operation); to funding for studies and projects; and to revenue sufficiency charges to cover costs of services (Shanaghan et al, 1998). Budgetary support for particular efforts and programs strongly influences capacity because of its impact on salary levels, operating expenses, and related priorities (Grindle and Hilderbrand, 1995).…”
Section: Resource Contextmentioning
confidence: 99%